Design, Synthesis and Activity Evaluation of Some Novel Indole Derivatives - He, Dian; Yang, Zhu-Qing; Hou, Meng (Asian Journal of Chemistry, 2015)
A series of novel indole derivatives as CDK4 inhibitors were designed and synthesized though the condensation reaction between the indolic acid and the corresponding substituted amine. The key step of our synthetic process is the efficient condensation reaction conducted by two different methods. The MTT and kinase assays were conducted used to assess the antitumor activity and cyclin-dependent kinases (CDKs) inhibitory activity. The most active compound 8b has an IC50 of 10-25 μM for the inhibition of four different tumor cells and CDK4. The higher activities of 8b were influenced by more conformational freedom resulted form the non-planar structure and by the stronger hydrogen bonding capability. Thus, the strategy we adapt to design potent, non-toxic CDK4 inhibitors is successful.